Sequential irrigation scheduling avoiding night irrigation - Anwar, Arif A.; Vries, T.T. de (American Society of Civil Engineers, 2017)
The sequential irrigation scheduling problem is one where a set of irrigation jobs have to be scheduled sequentially. In this paper, an integer program is presented to solve this problem. The objective function is a dual-goal function that avoids night irrigation and minimizes earliness or tardiness, with the former objective taking priority over the latter. A scheduled start time cost function is introduced and is user defined to reflect the behavior and preferences (and aversions) of farmers. In this paper, the scheduled start time cost function is a piecewise linear function and uses techniques from operations research. It is linearized using the disjunctive method. The integer program is implemented in a general-purpose solver and applied to a 16-job problem to demonstrate that a schedule can be prepared that avoids night irrigation and minimizes earliness and tardiness. There is a trade-off between avoiding night irrigation and earliness and tardiness compared to earlier models that minimize only earliness and tardiness. However, the increase in earliness and tardiness for the example presented is modest.